Methacryloyloxycalix[4]Arene Based Ion Imprinted Polymer As Ag(I) Potentiometric Sensor - Sener, Izzet; Avci, Seyma; Ugurag, Deniz; Ozkutuk, Ebru Birlik (Aperta, 2018)
A new potentiometric sensor for the rapid, easy and cheap determination of Ag(I) ions is proposed. This sensor has been prepared via suspension polymerization using ethylene glycol dimethacrylic acid (EDMA) as cross-linker, 2, 2-azobisisobutyronitrile (AIBN) as initiator and methacryloyloxycalix[4]arene as the monomer. The ion imprinted polymer-based Ag(I) memory sensor has been prepared by dispersing Ag(I) imprinted polymer throughout the DBP plasticizer and embedding in PVC. The sensor responds to Ag(I) in the pH range of 2.0-8.0 with a working range of 1.0x10(-3) - 1.0x10(-7) M and detection limit of 1.53x10(-8) M.